Añora, Spanien. Der Fundplatz ‚La Losilla‘ bei Añora (Córdoba) – eine spätantike Kirche im ländlichen Bereich der Baetica - Schlimbach, Fedor (e-Forschungsberichte des DAI, 2017)
The project addresses the remains of a late antique church at ‚La Losilla‘ near the town of Añora (Córdoba) in Andalusia. Besides these remains, the study of the adjacent cemetery is part of the project. One main goal is the archaeological examination of the context, in which the church was built and used – an aspect rather neglected during the work of the previous decades. After having realized two campaigns for the evaluation of the archaeological potential of the site in 2013 and 2014, we started its systematic excavation in the context of an investigation project with a duration of five years in 2015. The present article resumes the results of the second excavation campaign within this project.